FOUNDATIONS OF RESUSCITATION: SCIENTIFIC-THEORETICAL AND PRACTICAL ASPECTS (International journal of medical sciences, 2026)
Resuscitation is the process of providing emergency care necessary to save life. Resuscitation is the process of providing emergency care necessary to save life. This article discusses the scientific-theoretical and practical aspects of resuscitation. The main approaches to the resuscitation process, special strategies for children with developmental disabilities, and ethical issues important for medical professionals are considered.